Sorption Behavior of Cu(II) From Acidic SolutionUsing Weathered Basalt Andesite Products - Rajesh Singh; Ajay V. Shah; Bhavna A. Shah (E-Journal of Chemistry)
Wastewater discharged from electroplating industry pose a serioushazard due to their heavy metal load. The objective of this work is to evaluatethe removal of Cu(II) from acidic solution by sorption onto Weathered BasaltAndesite Products (WBAP). WBAP has been characterized and utilized forremoval of copper from aqueous solution over wide range of initial metal ionconcentration (25 mg/L to 500 mg/L), contact duration (0-8 h), sorbent dose(5-35 g/L), pH (1.0 to 6.0), and temperature (276 K to 333 K). The sorptionpattern of Cu ions onto WBAP followed Langmuir, Freundlich, and Dubinin-Kaganer-Radushkevich isotherms. The thermodynamic parameters (∆H0, ∆S0,and ∆G0) for Cu sorption onto WBAP were also determined.